Complications in sefel-injection of chemicals to increase muscle - Francisco Felipe Laitano; Anajara Gazzale; Evandro José Siqueira; Pedro Djacir Escobar Martins; Milton Paulo de Oliveira (Revista Brasileira de Cirurgia Plástica, 2016)
The number of gym goers who self-inject oily substances to increase muscle volume artificially and thereby improve the aesthetic appearance of their muscles that are unresponsive to training is increasing. Although immediate effects and satisfactory aesthetic results such as increased volume or changes in the contour of several areas of the body might be observed, oil infiltration might cause several short- and long-term complications, which are often irreversible. The awareness and actions of medical and health professional societies are fundamental for the prevention and control of this problem. In this article, possible complications are reviewed, and the case of a patient with severe local complications caused by oil injection is reported.